EBK NONLINEAR DYNAMICS AND CHAOS WITH S
EBK NONLINEAR DYNAMICS AND CHAOS WITH S
2nd Edition
ISBN: 9780429680151
Author: STROGATZ
Publisher: VST
bartleby

Concept explainers

bartleby

Videos

Question
Book Icon
Chapter 5.1, Problem 9E
Interpretation Introduction

Interpretation:

To sketch the vector field x˙ = -y, y˙ = -x. To show that the trajectories of the system are hyperbolas of the form x2 - y2 = C. The equations for the stable and unstable manifolds of the origin is to be found. To rewrite the system in terms of new variables u and v, and to solve for u(t) and v(t), starting from an arbitrary initial condition (u0, v0). The equations for the stable and unstable manifolds in terms of u and v is to be found. To write the general solution for x(t) and y(t), starting from an initial condition (x0, y0).

Concept Introduction:

The system assigns a vector (x˙y˙) at each point (x, y), and represents a vector field on the phase plane.

Substitute the given system in the equation xx˙ - yy˙ = 0 to show that the trajectories of the system are hyperbolas of the form x2 - y2 = C

The stable manifold of a fixed point is the set of all points in the plane which tends to the fixed point as time goes to positiveinfinity.

The unstable manifold for a fixed point is the set of all points in the plane which tends to the fixed point as time goes to negative infinity.

Expert Solution & Answer
Check Mark

Answer to Problem 9E

Solution:

a) The vector field of the system x˙ = -y, y˙ = -x is sketched

b) It is shown that the trajectories of the system are hyperbolas of the form x2 - y2 = C

c) The equations for the stable and unstable manifolds for origin are y = x and y = -x respectively.

d) The solutions in terms of new variables u and v, for the initial condition (u0, v0) are u(t) = u0 e- t and v(t) = v0 et.

e) The equations for the stable and unstable manifolds in terms of u and v are v = 0 and u = 0 respectively.

f) The general solution for x(t) and y(t) is x(t) = (x0 + y0) e- t + (x0 - y0) et2 and y(t) = (x0 + y0) e- t - (x0 - y0) et2 respectively.

Explanation of Solution

a) The vector field of the given system x˙ = -y, y˙ = -x is shown below

EBK NONLINEAR DYNAMICS AND CHAOS WITH S, Chapter 5.1, Problem 9E

b) Consider the given system,

x˙ = -y, y˙ = -x.

It can be shown that the trajectories of the system are hyperbolas of the form x2 - y2 = C by using the equation,

xx˙ - yy˙ = 0

Substituting -y for x˙, and -x for y˙

(x)(-y) - (y)(-x) = 0

-xy + xy = 0

Thus, the given system implies xx˙ - yy˙ = 0

Integrating the above equation,

(xx˙ - yy˙) dt = 0 dt

x2xdx = y2ydy

x2 - x22 = y2 - y22 + C

x2 - y2 = C

Thus, the trajectory of the given system is the hyperbola of the form x2 - y2 = C.

c) The origin is a saddle point for the given system. From the sketch of the vector field, it is clear that the equation y = x has vectors going towards the center or the fixed point, and is decaying. This means that the equation y = x is the stable manifold.

Also, the equation y = -x has vectors going away from the center or the fixed point, and is growing. This means the equation y = -x is the unstable manifold.

This can also be proved by substituting x for y and y for x in the given equations,

x˙ = -x and y˙ = -y

This linear system gives a stable fixed point.

Similarly, substituting -x for y and -y for x in the given equations,

x˙ = x and y˙ = y

This linear system gives an unstable fixed point.

Therefore, the equations for the stable and unstable manifolds for origin is y = x and y = -x respectively.

d) Introducing new variables u and v such that

u = x + y and v = x - y

The system can be rewritten as

u˙ = x˙ + y˙ and v˙ = x˙ - y˙

Substituting -y for x˙ and -x for y˙ in u˙ = x˙ + y˙,

u˙ = -y - xu˙ = -(x + y)

Again, substituting u for (x + y),

u˙ = - u

The above equation can be also represented as

u(t) = ce- t

Solving for the initial conditions,

Substituting t = 0 in u(t) = ce-t

u0 = ce0u0 = c

Substituting the value of c back in the equation u(t) = ce-t,

u(t) = u0 e- t

Similarly substituting -y for x˙ and -x for y˙ in v˙ = x˙ - y˙,

v˙ = -y + xv˙ = x - y

Again, substituting v for (x - y)

v˙ = v

The above equation can be also represented as

v(t) = cet

Solving for the initial conditions,

Substituting t = 0 in v(t) = cet,

v0 = ce0v0 = c

Substituting the value of c back in the equation v(t) = cet,

v(t) = v0 et

Hence, the solutions of the linear equation for the initial condition (u0, v0) is u(t) = u0 e- t and v(t) = v0 et.

e) Since the equations of the stable and unstable manifold are y = x and y = -x respectively.

Therefore, substituting y for x in the equation v = x - y,

v = y - yv = 0

Similarly, substituting -y for x in u = x + y,

u = -y + yu = 0

Thus, v = 0 and u = 0 are stable and unstable manifolds respectively in terms of u and v

f) Since u = x + y and v = x - y.

Solving the above equations to get the values of x and y in terms of u and v,

x = u + v2 and y = u - v2

Substituting u(t) = u0 e-t and v(t) = v0 et in x = u + v2,

x = u0e- t + v0et2

Again, substituting (x0+ y0) for u0 and (x0 - y0) for v0

x = (x0+ y0) e- t + (x0- y0) et2

Similarly, substituting u0e- t for u and v0et for v in y =u - v2,

y = u0e- t - v0et2

Again, substituting (x0+ y0) for u0 and (x0 - y0) for v0,

y = (x0+ y0) e- t - (x0- y0) et2

Therefore, the general solution for x(t) and y(t) is x(t) = (x0 + y0) e- t + (x0 - y0) et2 and y(t) = (x0 + y0) e- t - (x0 - y0) et2 respectively.

Want to see more full solutions like this?

Subscribe now to access step-by-step solutions to millions of textbook problems written by subject matter experts!
Students have asked these similar questions
(^) k Recall that for numbers 0 ≤ k ≤ n the binomial coefficient (^) is defined as n! k! (n−k)! Question 1. (1) Prove the following identity: (22) + (1121) = (n+1). (2) Use the identity above to prove the binomial theorem by induction. That is, prove that for any a, b = R, n (a + b)" = Σ (^) an- n-kyk. k=0 n Recall that Σ0 x is short hand notation for the expression x0+x1+ +xn- (3) Fix x = R, x > 0. Prove Bernoulli's inequality: (1+x)" ≥1+nx, by using the binomial theorem. - Question 2. Prove that ||x| - |y|| ≤ |x − y| for any real numbers x, y. Question 3. Assume (In) nEN is a sequence which is unbounded above. That is, the set {xn|nЄN} is unbounded above. Prove that there are natural numbers N] k for all k Є N. be natural numbers (nk Є N). Prove that
not use ai please
3) Let G be the group generated by elements a and b satisfying the relations a² = 63, 66 = 1, and a ¹ba = b¹. Which of the following is equivalent to the element z = a a-2ba3b3? A) b-2a-1 B) ab² C) ab D) ba E) b²a
Knowledge Booster
Background pattern image
Advanced Math
Learn more about
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, advanced-math and related others by exploring similar questions and additional content below.
Similar questions
SEE MORE QUESTIONS
Recommended textbooks for you
Text book image
Elementary Linear Algebra (MindTap Course List)
Algebra
ISBN:9781305658004
Author:Ron Larson
Publisher:Cengage Learning
Text book image
Elementary Geometry For College Students, 7e
Geometry
ISBN:9781337614085
Author:Alexander, Daniel C.; Koeberlein, Geralyn M.
Publisher:Cengage,
Vector Spaces | Definition & Examples; Author: Dr. Trefor Bazett;https://www.youtube.com/watch?v=72GtkP6nP_A;License: Standard YouTube License, CC-BY
Understanding Vector Spaces; Author: Professor Dave Explains;https://www.youtube.com/watch?v=EP2ghkO0lSk;License: Standard YouTube License, CC-BY